Penerapan model pembelajaran giving question getting answer (GQGA) untuk meningkatkan keaktifan dalam pembelajaran IPS pada peserta didik kelas IV sekolah dasar - Putri, Novilia; Istiyati, Siti; Yulianti, Yulianti (Didaktika Dwija Indria, 2020)
The purpose of this study is to improve the activeness in IPS learning by applying Giving Question Getting Answer learning model. Type of this study is a classroom action research with two cycles, each of which consisting four stages: planning, acting, observing, and reflecting. This study was conducted in IVA grade students of SD Djama’atul Ichwan in the school year of 2019/2020. The subjects of this study were 29 students and class teacher. Data collection techniques include interviews, observation, documentation, and questionnaires. Data validity testing techniques performed using content validity and techniques triangulation. Data analysis techniques used is Miles-Huberman interactive analysis model. Observations resulted in a percentage of 20,69% in pre-action, 51,72% in the first cycle, and 86,21% in the second cycle. Questionnaire produced a percentage of 24,14% in pre-action, 72,41% in the first cycle, and 86,21% in the second cycle. The contribution of this study is that teachers can apply the GQGA learning model to the learning process to increase learning activeness. The conclusion of this study is that the application of Giving Question Getting Answer learning model can improve the activeness in IPS learning of IVA grade students at SD Djama’atul Ichwan in the school year of 2019/2020.